Sekolah Ramah Anak Berintegritas Pesantren - Muhammad Abdul Latif; Muh. Hasyim Rosyidi; Rosyidatul Khoiriah (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2021)
The holding of a child-friendly school with Islamic boarding school integrity because of the support from the community, government and foundations to uphold the rights and obligations of children in learning, and a pesantren program to provide provisions for students to socialize. This study uses a qualitative research type of data collection methods used in the form of observation, interviews, documentation. The results of the study indicate that the implementation of the Child Friendly School Program with Islamic Boarding Schools includes: school principals have provided special training to educators so that they can understand what must be done in implementing child-friendly schools with pesantren integrity, including planning, implementation and monitoring. (1) The planning of the Child-Friendly Schools with Islamic Boarding Schools program begins with a meeting between the Principal and the committee and staff related to the Child-Friendly School Program, the meeting discusses planning and evaluating the program. (2) The implementation of the policy for the Child-Friendly Schools with Integrity for Islamic Boarding Schools must meet several components, such as the completeness of infrastructure, children's participation, parental participation, and community participation. Therefore, the implementation of the Child Friendly School program policy really involves all school residents, and the completeness of adequate infrastructure, an appropriate curriculum and trained education personnel for children's rights. (3) It aims to obtain the results of the implementation of the Child Friendly School program and as a determinant of planning and subsequent programs. Supporting factors in the implementation of the Islamic Boarding School Integrity Child Friendly School program, namely in addition to adequate facilities, it also received strong support from the Government, donors and foundations. The inhibiting factor for the running of Child Friendly Schools is that there are still thoughts from students who feel insecure and also comfortable in learning.